#TITLE_ALTERNATIVE# - NURHAKIM (NIM : 10209039), RAHMAN
Sumatran fault is one of the active faults located in Indonesia. This fault is formed as a result of the convergence between the Indo-Australian and Eurasian plates. This fault extends from the north-side to the south-side of Sumatra Island. Some of geophysics methods have been carried out to study this Sumatran fault, such as GPS and seismic. This research uses the Magnetotelluric method to map the beneath surface at the fault zone. Magnetotelluric method is one of the geophysics method that can map the beneath surface with the resistivity distribution as the parameter. This method has a deep penetration; up to hundreds of kilometres, but in the other hand it make the resolution becomes low. This research has been performed from 2009 and in August 2013 a measurement is carried out at some points that intersect the fault by measuring the intensity of the electric field and magnetic field at each point. The data processing was done with the support of the software SSMT2000, MTEditor and MATLAB. Inversion modeling is carried out to process data using the Microsoft Fortran PowerStation and Microsoft Developer Studio. The inversion method that is used in this research is the Least Square Inversion method. The results show that the fault zone has been characterized by a contrast resistivity in the area around the fault, and that there is a layer close to surface that has a high resistivity.